PERUBAHAN PENGGUNAAN LAHAN DAN KEBUTUHAN LAHAN PERMUKIMAN DI KOTA BONTANG, KALIMANTAN TIMUR - Muji Esti Wahyudi; Khursatul Munibah; Widiatmaka Widiatmaka (Diponegoro University, 2019)
Bontang is the youngest city in East Kalimantan which focused to industrial sector. As the industry city, Bontang has been growing rapidly especially for population and regional development. This study was aimed to (a) identified land use in Bontang at 2002, 2009 and 2016 (b) analyze land use change and land use prediction in 2023 (c) evaluate land suitability and availability for settlement and (d) to estimate the land required for settlement in Bontang. The research was conducted by overlay method, matching system based on minimum limiting factor and descriptive analysis. Results analysis showed that actual land use in Bontang (2016) was dominated by bush, forest, mangrove, settlement, industry and plantation area. Dominant land use change (2002-2016) in Bontang was forest to bush. The area of settlement in 2016 was about 1.770 ha and predicted to be the highest increased compared to other land use in 2023. Land suitability analysis showed that 4.864 ha or 30,71% of this region was in suitable class fo settlement. The availability of suitable land settlement exclude the existing was about 941,5 ha, which could meet the needs of settlement up to 2050.